Method and device for rapidly evaluating suitability of aluminum plastic film and electrolyte

By testing the melting point, infrared spectrum and peeling force of aluminum-plastic film before and after the electrolyte, combined with the effect of the two-seal sol, the adaptability of the electrolyte and aluminum-plastic film was determined, and the failure to effectively evaluate the electrolyte to aluminum in the prior art was solved. The problem of the impact of plastic film has achieved the best adaptability evaluation of aluminum-plastic film and electrolyte, and improved the stability and safety of lithium-ion batteries.

CN119290739APending Publication Date: 2025-01-10SHENZHEN HIGHPOWER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411394717.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art has failed to effectively evaluate the impact of different functional electrolytes on aluminum-plastic films, affect the stability and safety of soft-pack lithium-ion batteries, and has failed to determine the optimal adaptability of aluminum-plastic films and electrolytes.

Method used

By testing the melting point, infrared spectrum, peeling force between the PP layer and the aluminum layer and the tension of the double-seal sol of the aluminum-plastic film before and after the electrolyte, the threshold value is set to judge the adaptability of the electrolyte and the aluminum-plastic film, and a rapid evaluation method and device are provided. , including DSC differential scanning calorimeter, infrared chromatograph, tensioner and battery two-packing machine.

Benefits of technology

The optimal adaptability evaluation of aluminum-plastic film and electrolyte is achieved, ensuring adaptability before packaging and in the two-package state, and improving the stability and safety of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119290739A_ABST
    Figure CN119290739A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery production, and discloses a method and a device for rapidly evaluating the suitability of an aluminum plastic film and an electrolyte. The method comprises the following steps: judging whether F3 / F1 is greater than a preset first threshold value and F4 / F2 is greater than a preset second threshold value if the melting point, infrared chromatography and secondary sealing sol effect of a to-be-adapted aluminum plastic film are not changed before and after the to-be-adapted aluminum plastic film is soaked in a to-be-adapted electrolyte; if yes, the electrolyte to be adapted is judged to be the electrolyte adapted to the aluminum plastic film to be adapted; and if not, the electrolyte to be adapted is judged to be the electrolyte which is not adapted to the aluminum plastic film to be adapted. According to the method, not only is the suitability of the aluminum plastic film and the electrolyte before packaging determined, but also the suitability of the aluminum plastic film in the secondary packaging state and the electrolyte is determined, so that the optimal suitability of the aluminum plastic film and the electrolyte is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery production, and in particular to a method and a device for quickly evaluating the compatibility of an aluminum-plastic film and an electrolyte. Background Art

[0002] The aluminum-plastic film used in soft-package lithium-ion batteries is generally composed of nylon, aluminum layer and PP (polypropylene) layer. In order to ensure that the soft-package lithium-ion battery can operate stably for a long time, the aluminum-plastic film needs to have extremely high barrier properties, good cold stamping formability, electrolyte corrosion resistance and insulation, etc. In the production process of soft-package lithium-ion batteries, the cell packaging is divided into packaging before liquid injection and packaging after liquid injection. The inner layer of the aluminum-plastic film after liquid injection contacts the electrolyte. Under the immersion of the electrolyte, the electrolyte exists inside the PP layer, which not only affects the peeling force between the PP layer and the aluminum layer, but also affects the secondary sealing effect after liquid injection. Therefore, the introduction of the electrolyte makes the secondary packaging of the aluminum-plastic film with liquid injection complicated. During the secondary packaging, the electrolyte will remain at the secondary seal, affecting the effect of the secondary seal.

[0003] With the diversification of product functions, electrolytes are becoming more and more complex. Different electrolytes have different solvents and additives, and their effects on aluminum-plastic film after injection will also be different. At present, the practice adopted in the industry is to evaluate the electrolyte resistance of aluminum-plastic film based on the effect of the immersion time of aluminum-plastic film in electrolyte on the peeling strength between PP layer and aluminum layer.

[0004] It can be seen that the prior art does not consider: the influence of different functional electrolytes on other properties of the aluminum-plastic film (such as melting point, infrared spectrum, etc.), and the influence of different functional electrolytes on the packaging effect of the aluminum-plastic film after immersion; and these are factors that can affect the stability and safety of soft-pack lithium-ion batteries. In view of this, in order to achieve the best adaptation of the aluminum-plastic film and the electrolyte, it is necessary for technical personnel in this field to further study the adaptability of different electrolytes to the secondary sealing of the aluminum-plastic film, not only to determine the adaptability of the aluminum-plastic film and the electrolyte before packaging, but also to determine the adaptability of the aluminum-plastic film and the electrolyte in the secondary sealing state. Summary of the invention

[0005] The object of the present invention is to provide a method and device for quickly evaluating the compatibility of an aluminum-plastic film and an electrolyte, so as to solve or at least partially solve the technical problems mentioned in the above background technology.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for quickly evaluating the compatibility of an aluminum-plastic film with an electrolyte, comprising:

[0008] The melting point and infrared spectrum of the aluminum-plastic film to be adapted are tested respectively before and after being immersed in the electrolyte to be adapted;

[0009] The peeling force between the PP layer and the aluminum layer of the aluminum-plastic film to be adapted is tested before and after being immersed in the electrolyte to be adapted;

[0010] The aluminum-plastic film to be adapted is double-sealed before and after being soaked in the electrolyte to be adapted, and the double-sealed sol tensile force and the double-sealed sol effect of the aluminum-plastic film to be adapted are tested before and after being soaked in the electrolyte to be adapted;

[0011] If the melting point, infrared spectrum and secondary sealing sol effect of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted do not change, it is determined whether F3 / F1 is greater than a preset first threshold value, and F4 / F2 is greater than a preset second threshold value;

[0012] If yes, it is determined that the electrolyte to be adapted is an electrolyte adapted to the aluminum-plastic film to be adapted;

[0013] If not, it is determined that the electrolyte to be adapted is an electrolyte that is not compatible with the aluminum-plastic film to be adapted;

[0014] Among them, the second threshold is greater than the first threshold; F1 is the peeling force between the PP layer and the aluminum layer of the aluminum-plastic film before being immersed in the electrolyte to be adapted, and F3 is the peeling force between the PP layer and the aluminum layer of the aluminum-plastic film after being immersed in the electrolyte to be adapted; F2 is the secondary sealing sol tensile force between the PP layer and the aluminum layer of the aluminum-plastic film before being immersed in the electrolyte to be adapted, and F4 is the secondary sealing sol tensile force between the PP layer and the aluminum layer of the aluminum-plastic film after being immersed in the electrolyte to be adapted.

[0015] Optionally, the first threshold is 0.8 and the second threshold is 0.9.

[0016] Optionally, the method of testing the melting point and infrared spectrum of the aluminum-plastic film to be adapted before and after immersion in the electrolyte to be adapted also includes:

[0017] Taking the aluminum-plastic film to be adapted, and using it to prepare a plurality of first test samples of predetermined sizes; and,

[0018] A plurality of aluminum-plastic film bags of the same size are prepared using the aluminum-plastic film to be adapted, and the electrolyte to be adapted is respectively injected into each of the aluminum-plastic film bags;

[0019] Soak the aluminum-plastic film bag filled with electrolyte in a predetermined ambient temperature for a predetermined time;

[0020] Cutting the aluminum-plastic film bag soaked in the electrolyte into a plurality of second test samples of the predetermined size; performing double sealing on the aluminum-plastic film to be adapted before and after soaking in the electrolyte to be adapted, and testing the double sealing sol tensile force and double sealing sol effect of the aluminum-plastic film to be adapted before and after soaking in the electrolyte to be adapted, specifically includes:

[0021] Under the predetermined second-sealing parameters, the first test sample is second-sealed to test the second-sealing sol effect and the second-sealing sol tensile force of the first test sample;

[0022] Under the second sealing parameters, the second test sample is second sealed to test the second test sample's second sealing sol effect and second sealing sol tension.

[0023] Optionally, the melting point and infrared spectrum of the aluminum-plastic film to be adapted are tested before and after being immersed in the electrolyte to be adapted, specifically:

[0024] testing the melting point and infrared spectrum of the first test sample and the second test sample respectively;

[0025] The melting point was tested by differential scanning calorimetry.

[0026] Optionally, the step of testing the peeling force between the PP layer and the aluminum layer of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted specifically includes:

[0027] The PP layer and the aluminum layer of the first test sample are clamped at two ends of the tensile testing machine respectively, and the two ends of the tensile testing machine are controlled to peel and stretch at a predetermined speed, and the peeling force between the PP layer and the aluminum layer of the first test sample is measured;

[0028] The PP layer and the aluminum layer of the second test sample are clamped at two ends of the tensile testing machine respectively, and the two ends of the tensile testing machine are controlled to peel and stretch at a predetermined speed, and the peeling force between the PP layer and the aluminum layer of the second test sample is measured;

[0029] Wherein, the predetermined speed is 50 mm / min.

[0030] Optionally, the secondary sealing parameters include: an upper sealing head temperature of 185° C., a lower sealing head temperature of 180° C., a packaging pressure of 0.4 MPa, and a packaging time of 4 seconds.

[0031] Optionally, the first test sample is a square aluminum-plastic film, and the predetermined size is 100 mm long*15 mm wide.

[0032] Optionally, the aluminum-plastic film bag filled with electrolyte is immersed in a predetermined ambient temperature for a predetermined time, specifically: the aluminum-plastic film bag filled with electrolyte is immersed in an ambient temperature of 30 to 85° C. for 24 to 72 hours;

[0033] The step of cutting the aluminum-plastic film bag soaked in the electrolyte into a plurality of second test samples of the predetermined size specifically comprises:

[0034] After the aluminum-plastic film bag filled with electrolyte is immersed in a predetermined ambient temperature for a predetermined time, the electrolyte is poured out;

[0035] The portion of the aluminum-plastic film bag soaked in the electrolyte was cut into a number of second test samples in a square shape with a size of 100 mm long and 15 mm wide.

[0036] Optionally, if the melting point, infrared spectrum and second sealing sol effect of the aluminum-plastic film to be adapted do not change before and after being immersed in the electrolyte to be adapted, before judging whether F3 / F1 is greater than a preset first threshold value and F4 / F2 is greater than a preset second threshold value, the method further includes:

[0037] Compare the melting point, infrared spectrum and secondary sealing sol effect of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted to determine whether there is no change;

[0038] If so, determine whether F3 / F1 is greater than a preset first threshold, and F4 / F2 is greater than a preset second threshold;

[0039] If not, it is determined that the electrolyte to be adapted is an electrolyte that is not compatible with the aluminum-plastic film to be adapted.

[0040] In a second aspect, the present invention provides a device for quickly evaluating the compatibility of an aluminum-plastic film with an electrolyte, comprising:

[0041] DSC differential scanning calorimeter, used to measure the melting point of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted;

[0042] Infrared chromatograph, used to test the melting point and infrared spectrum of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted;

[0043] A tensile testing machine is used to test the peeling force between the PP layer and the aluminum layer of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted, and to test the tensile force of the second sealing sol of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted;

[0044] A battery secondary sealing machine is used to perform secondary sealing on the aluminum-plastic film to be adapted before and after being soaked in the electrolyte to be adapted;

[0045] A camera assembly, used to photograph the secondary sol effect of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted;

[0046] A data processing terminal equipped with a display module is used to compare the melting point, infrared spectrum and second-sealing sol effect of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted, to determine whether there is no change; and to determine whether F3 / F1 is greater than a preset first threshold, and F4 / F2 is greater than a preset second threshold;

[0047] The data processing terminal is used to display a first prompt message on its display module when the melting point, infrared spectrum and second sealing sol effect of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted change, and / or F3 / F1 is less than or equal to a preset first threshold, and / or F4 / F2 is less than or equal to a preset second threshold; otherwise, display a second prompt message on its display module;

[0048] The first prompt information is used to prompt that the electrolyte to be adapted is an electrolyte that is not compatible with the aluminum-plastic film to be adapted, and the second prompt information is used to prompt that the electrolyte to be adapted is an electrolyte that is compatible with the aluminum-plastic film to be adapted;

[0049] Among them, the second threshold is greater than the first threshold; F1 is the peeling force between the PP layer and the aluminum layer of the aluminum-plastic film before being immersed in the electrolyte to be adapted, and F3 is the peeling force between the PP layer and the aluminum layer of the aluminum-plastic film after being immersed in the electrolyte to be adapted; F2 is the secondary sealing sol tensile force between the PP layer and the aluminum layer of the aluminum-plastic film before being immersed in the electrolyte to be adapted, and F4 is the secondary sealing sol tensile force between the PP layer and the aluminum layer of the aluminum-plastic film after being immersed in the electrolyte to be adapted.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] The present invention confirms the compatibility of the aluminum-plastic film and the electrolyte before packaging by testing the melting point, infrared spectrum, and peeling force of the PP layer and the aluminum layer of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte and comparing them; and confirms the compatibility of the aluminum-plastic film and the electrolyte in the double-sealed state by comparing the double-sealed sol effect and the packaging strength of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte; not only the compatibility of the aluminum-plastic film and the electrolyte before packaging is determined, but also the compatibility of the aluminum-plastic film and the electrolyte in the double-sealed state is determined, thereby achieving the best adaptation of the aluminum-plastic film and the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0053] Figure 1 A flow chart of a method for quickly evaluating the compatibility of an aluminum-plastic film and an electrolyte provided in an embodiment of the present invention.

[0054] Figure 2 A comparison diagram of the melting points of an aluminum-plastic film to be adapted before and after being immersed in different electrolytes provided in an embodiment of the present invention.

[0055] Figure 3A comparison diagram of the sol effects of an aluminum-plastic film to be adapted before and after being immersed in different electrolytes provided in an embodiment of the present invention.

[0056] Figure 4 A comparison diagram of infrared spectra of an aluminum-plastic film to be adapted before and after being immersed in different electrolytes provided in an embodiment of the present invention.

[0057] Figure 5 A data display diagram of the peeling force and the secondary sealing sol tensile force of an aluminum-plastic film to be adapted before and after being immersed in different electrolytes provided in an embodiment of the present invention.

[0058] Figure 6 A comparison chart of long-term storage test results of battery cells prepared with different electrolytes using an aluminum-plastic film to be adapted provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0059] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0060] Embodiment 1:

[0061] Please refer to Figure 1 , Figure 1 A flow chart of a method for quickly evaluating the compatibility of an aluminum-plastic film and an electrolyte provided in an embodiment of the present invention; before the method is officially carried out, it is necessary to prepare samples for testing, namely, the method includes:

[0062] Preset step 101: take the aluminum-plastic film to be adapted and use it to prepare a plurality of first test samples of predetermined sizes.

[0063] For example, the first test sample in step 101 is a square aluminum-plastic film with a predetermined size of 100 mm long*15 mm wide. This embodiment will be described by taking a commonly used dry-process 113 aluminum-plastic film on the market as an example.

[0064] Preset step 102: prepare a plurality of aluminum-plastic film bags of the same size using the aluminum-plastic film to be adapted, and inject the electrolyte to be adapted into each aluminum-plastic film bag respectively.

[0065] In order to quickly select the electrolyte that matches the aluminum-plastic film, the present embodiment can prepare a plurality of aluminum-plastic film bags in advance and inject different electrolytes (containing 1000ppm water content) into them respectively;

[0066] For example, in this embodiment, the size of the aluminum-plastic film bag is 100*150 mm, and the electrolyte to be adapted is selected from four commercial electrolytes with different functions: A, B, C, and D.

[0067] Preset step 103: soak the aluminum-plastic film bag filled with electrolyte in a predetermined ambient temperature for a predetermined time.

[0068] In this embodiment, the ambient temperature can be selected to be 30 to 85°C, and the soaking time can be set to be 24 to 72 hours;

[0069] Exemplarily, step 103 specifically includes: soaking the aluminum-plastic film bag filled with electrolyte in an ambient temperature of 85° C. for 24 hours.

[0070] Preset step 104, cutting the aluminum-plastic film bag soaked in electrolyte into a plurality of second test samples of predetermined sizes. Specifically comprising:

[0071] After the aluminum-plastic film bag filled with electrolyte is immersed in a predetermined ambient temperature for a predetermined time, the electrolyte is poured out;

[0072] The portion of the aluminum-plastic film bag soaked in the electrolyte was cut into a number of second test samples in a square shape with a size of 100 mm long and 15 mm wide.

[0073] After preparing the corresponding test samples, you can officially start testing the relevant parameters, as follows:

[0074] Step 110, respectively testing the melting point and infrared spectrum of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted.

[0075] like Figure 2 and Figure 4 As shown, Figure 2 A comparison diagram of the melting points of an aluminum-plastic film to be adapted before and after being immersed in different electrolytes provided in an embodiment of the present invention, Figure 4 A comparison diagram of infrared spectra of an aluminum-plastic film to be adapted before and after being immersed in different electrolytes provided in an embodiment of the present invention.

[0076] Step 110 is specifically implemented as follows:

[0077] testing the melting point and infrared spectrum of the first test sample and the second test sample respectively;

[0078] In the detection of aluminum-plastic film, DSC (differential scanning calorimetry) test is an important means to determine the melting point of the material. This step uses DSC to test the melting point of the aluminum-plastic film to be adapted; Figure 2The melting point data of the aluminum-plastic film before and after being soaked in 4 kinds of electrolytes to be adapted are shown in the figure.

[0079] Figure 4 The infrared spectra of the aluminum-plastic film before and after being soaked in four kinds of electrolytes to be adapted are shown in FIG. Figure 4 It can be seen intuitively that after being soaked in electrolyte D, its infrared spectrum has a mixed peak in the dotted box.

[0080] Step 120, respectively testing the peeling force between the PP layer and the aluminum layer of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted. Specifically comprising:

[0081] The PP layer and the aluminum layer of the first test sample are clamped at two ends of the tensile testing machine respectively, and the two ends of the tensile testing machine are controlled to peel and stretch at a predetermined speed, and the peeling force F1 between the PP layer and the aluminum layer of the first test sample is measured;

[0082] The PP layer and the aluminum layer of the second test sample are clamped at two ends of the tensile testing machine respectively, and the two ends of the tensile testing machine are controlled to peel and stretch at a predetermined speed, and the peeling force F3 between the PP layer and the aluminum layer of the second test sample is measured;

[0083] Exemplarily, in step 120, the predetermined speed is 50 mm / min.

[0084] Step 130 , re-seal the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted.

[0085] The secondary sealing parameters include: upper head temperature of 185°C, lower head temperature of 180°C, packaging pressure of 0.4Mpa, and packaging time of 4S.

[0086] Step 140 , respectively testing the secondary sealing sol tensile force and secondary sealing sol effect of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted.

[0087] The test method of the tensile force of the second sealing sol in step 140 is the same as that in step 130, that is, the tensile force of the second sealing sol of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted is tested again by using a tensile testing machine;

[0088] For ease of description, F1 is defined as the peeling force between the PP layer and the aluminum layer of the aluminum-plastic film before soaking in the electrolyte to be adapted, F3 is defined as the peeling force between the PP layer and the aluminum layer of the aluminum-plastic film after soaking in the electrolyte to be adapted, F2 is the secondary sealing sol tensile force between the PP layer and the aluminum layer of the aluminum-plastic film before soaking in the electrolyte to be adapted, and F4 is the secondary sealing sol tensile force between the PP layer and the aluminum layer of the aluminum-plastic film after soaking in the electrolyte to be adapted;

[0089] Please continue to refer to Figure 3, which is the double-sealed sol effect of the aluminum-plastic film before and after being immersed in the electrolyte to be adapted, taken by the camera component.

[0090] Step 150 , comparing the melting point, infrared spectrum and secondary sol effect of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted, to determine whether there is no change; if so, executing step 170 ; if not, executing step 160 .

[0091] Step 160: Determine whether F3 / F1 is greater than a preset first threshold, and whether F4 / F2 is greater than a preset second threshold.

[0092] The second threshold is greater than the first threshold. In this embodiment, the first threshold is 0.8 and the second threshold is 0.8.

[0093] It is understandable that during the test process, due to the influence of environmental factors or test accuracy, the test results will have some errors to a greater or lesser extent, so an error threshold can be set in advance. For example, the error threshold of the melting point in this embodiment can be set to 2°C, that is, a melting point change within plus or minus 2°C will be regarded as no change in the melting point; of course, the setting of the error threshold needs to be specifically set according to the actual application situation. For example, if technological advances have made the measurement accuracy higher, the error threshold can be appropriately lowered at this time.

[0094] Step 170: Determine that the electrolyte to be adapted is an electrolyte adapted to the aluminum-plastic film to be adapted.

[0095] Step 180: Determine that the electrolyte to be adapted is an electrolyte that is not compatible with the aluminum-plastic film to be adapted.

[0096] Please refer to Figure 5 and Figure 6 , Figure 5 The data display diagram of the peeling force and the secondary sealing sol tensile force of an aluminum-plastic film to be adapted before and after being immersed in different electrolytes provided by an embodiment of the present invention, Figure 6 A comparison chart of long-term storage test results of a battery cell prepared by combining an aluminum-plastic film to be adapted provided by an embodiment of the present invention with different electrolytes;

[0097] according to Figure 5 It can be seen that electrolytes A, C and D are incompatible electrolytes, so the battery cells made with them leaked after 36 months, 24 months and 12 months respectively; from the long-term storage test results, electrolyte B is the electrolyte that is compatible with the aluminum-plastic film to be adapted.

[0098] In summary, according to Figure 2-Figure 5From the test data, it can be seen intuitively that the changes in the melting point of the aluminum-plastic film after being soaked in electrolytes A, B, C and D are all within the allowable error range; however, the infrared spectrum of the aluminum-plastic film after being soaked in electrolyte D changes, which can be used to determine that it is an incompatible electrolyte; in addition, after the aluminum-plastic film is soaked in electrolytes A, C and D, it cannot meet the conditions that F3 / F1 is greater than the preset first threshold and F4 / F2 is greater than the preset second threshold; therefore, among the above four electrolytes, only electrolyte B is the electrolyte that is compatible with the aluminum-plastic film to be adapted, and the other three are incompatible electrolytes; and according to Figure 5 The final verification results can also prove the accuracy of the above evaluation results.

[0099] It can be understood that in this embodiment, the sequence of some steps can be adjusted according to actual conditions. For example, the relevant data of the aluminum-plastic film after being immersed in the electrolyte can be tested first, and then the relevant data of the aluminum-plastic film before being immersed in the electrolyte can be tested. The tests can also be performed in a cross order. Therefore, in this embodiment, the sequence of steps cannot be regarded as a limitation on the scope of protection of the present invention.

[0100] This embodiment confirms the compatibility of the aluminum-plastic film and the electrolyte before packaging by testing the melting point, infrared spectrum, and peeling force of the PP layer and the aluminum layer of the aluminum-plastic film to be adapted before and after immersion in the electrolyte and comparing them; it also confirms the compatibility of the aluminum-plastic film and the electrolyte in the double-sealed state by comparing the double-sealed sol effect and the packaging strength of the aluminum-plastic film to be adapted before and after immersion in the electrolyte; not only the compatibility of the aluminum-plastic film and the electrolyte before packaging is determined, but also the compatibility of the aluminum-plastic film and the electrolyte in the double-sealed state is determined, thereby achieving the best adaptation of the aluminum-plastic film and the electrolyte.

[0101] Embodiment 2:

[0102] This embodiment provides a device for quickly evaluating the compatibility of an aluminum-plastic film and an electrolyte, comprising:

[0103] DSC differential scanning calorimeter, used to measure the melting point of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted;

[0104] Infrared chromatograph, used to test the melting point and infrared spectrum of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted;

[0105] A tensile testing machine is used to test the peeling force between the PP layer and the aluminum layer of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted, and to test the tensile force of the second sealing sol of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted;

[0106] A battery secondary sealing machine is used to perform secondary sealing on the aluminum-plastic film to be adapted before and after being soaked in the electrolyte to be adapted;

[0107] A camera assembly, used to photograph the secondary sol effect of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted;

[0108] A data processing terminal equipped with a display module is used to compare the melting point, infrared spectrum and second-sealing sol effect of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted, to determine whether there is no change; and to determine whether F3 / F1 is greater than a preset first threshold, and F4 / F2 is greater than a preset second threshold;

[0109] The data processing terminal is used to display a first prompt message on its display module when the melting point, infrared spectrum and secondary sol effect of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted change, and / or F3 / F1 is less than or equal to a preset first threshold, and / or F4 / F2 is less than or equal to a preset second threshold; otherwise, display a second prompt message on its display module;

[0110] The first prompt information is used to prompt that the electrolyte to be adapted is an electrolyte that is not compatible with the aluminum-plastic film to be adapted, and the second prompt information is used to prompt that the electrolyte to be adapted is an electrolyte that is compatible with the aluminum-plastic film to be adapted;

[0111] Among them, the second threshold is greater than the first threshold; F1 is the peeling force between the PP layer and the aluminum layer of the aluminum-plastic film before being immersed in the electrolyte to be adapted, and F3 is the peeling force between the PP layer and the aluminum layer of the aluminum-plastic film after being immersed in the electrolyte to be adapted; F2 is the secondary sealing sol tensile force between the PP layer and the aluminum layer of the aluminum-plastic film before being immersed in the electrolyte to be adapted, and F4 is the secondary sealing sol tensile force between the PP layer and the aluminum layer of the aluminum-plastic film after being immersed in the electrolyte to be adapted.

[0112] Since the method of using the device to evaluate the compatibility between the aluminum-plastic film and the electrolyte has been described in detail in the first embodiment, it will not be repeated in this embodiment.

[0113] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for quickly evaluating the compatibility of an aluminum-plastic film with an electrolyte, characterized in that: include: The melting point and infrared spectrum of the aluminum-plastic film to be adapted are tested respectively before and after being immersed in the electrolyte to be adapted; The peeling force between the PP layer and the aluminum layer of the aluminum-plastic film to be adapted is tested before and after being immersed in the electrolyte to be adapted; The aluminum-plastic film to be adapted is double-sealed before and after being soaked in the electrolyte to be adapted, and the double-sealed sol tensile force and the double-sealed sol effect of the aluminum-plastic film to be adapted are tested before and after being soaked in the electrolyte to be adapted; If the melting point, infrared spectrum and secondary sealing sol effect of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted do not change, it is determined whether F3 / F1 is greater than a preset first threshold value, and F4 / F2 is greater than a preset second threshold value; If yes, it is determined that the electrolyte to be adapted is an electrolyte adapted to the aluminum-plastic film to be adapted; If not, it is determined that the electrolyte to be adapted is an electrolyte that is not compatible with the aluminum-plastic film to be adapted; Wherein, the second threshold is greater than the first threshold; F1 is the peeling force between the PP layer and the aluminum layer of the aluminum-plastic film before being immersed in the electrolyte to be adapted, and F3 is the peeling force between the PP layer and the aluminum layer of the aluminum-plastic film after being immersed in the electrolyte to be adapted; F2 is the secondary sol tensile force between the PP layer and the aluminum layer of the aluminum-plastic film before it is immersed in the electrolyte to be adapted, and F4 is the secondary sol tensile force between the PP layer and the aluminum layer of the aluminum-plastic film after it is immersed in the electrolyte to be adapted.

2. The method for rapidly evaluating the compatibility of an aluminum-plastic film with an electrolyte according to claim 1, characterized in that: The first threshold is 0.8, and the second threshold is 0.

9.

3. The method for rapidly evaluating the compatibility of an aluminum-plastic film with an electrolyte according to claim 2, characterized in that: The method of testing the melting point and infrared spectrum of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted also includes: Taking the aluminum-plastic film to be adapted, and using it to prepare a plurality of first test samples of predetermined sizes; and, A plurality of aluminum-plastic film bags of the same size are prepared using the aluminum-plastic film to be adapted, and the electrolyte to be adapted is respectively injected into each of the aluminum-plastic film bags; Soak the aluminum-plastic film bag filled with electrolyte in a predetermined ambient temperature for a predetermined time; Cutting the aluminum-plastic film bag soaked in the electrolyte into a plurality of second test samples of the predetermined size; The second sealing of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted is respectively performed, and the second sealing sol tensile force and the second sealing sol effect of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted are tested, specifically including: Under the predetermined second-sealing parameters, the first test sample is second-sealed to test the second-sealing sol effect and the second-sealing sol tensile force of the first test sample; Under the second sealing parameters, the second test sample is second sealed to test the second test sample's second sealing sol effect and second sealing sol tension.

4. The method for rapidly evaluating the compatibility of an aluminum-plastic film with an electrolyte according to claim 3, characterized in that: The melting point and infrared spectrum of the aluminum-plastic film to be adapted are tested before and after being immersed in the electrolyte to be adapted, specifically: testing the melting point and infrared spectrum of the first test sample and the second test sample respectively; The melting point was tested by differential scanning calorimetry.

5. The method for rapidly evaluating the compatibility of an aluminum-plastic film with an electrolyte according to claim 3, characterized in that: The testing of the peeling force between the PP layer and the aluminum layer of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted specifically includes: The PP layer and the aluminum layer of the first test sample are clamped at two ends of the tensile testing machine respectively, and the two ends of the tensile testing machine are controlled to peel and stretch at a predetermined speed, and the peeling force between the PP layer and the aluminum layer of the first test sample is measured; The PP layer and the aluminum layer of the second test sample are clamped at two ends of the tensile testing machine respectively, and the two ends of the tensile testing machine are controlled to peel and stretch at a predetermined speed, and the peeling force between the PP layer and the aluminum layer of the second test sample is measured; Wherein, the predetermined speed is 50 mm / min.

6. The method for rapidly evaluating the compatibility of an aluminum-plastic film with an electrolyte according to claim 3, characterized in that: The secondary sealing parameters include: upper head temperature of 185° C., lower head temperature of 180° C., packaging pressure of 0.4 MPa, and packaging time of 4 seconds.

7. The method for rapidly evaluating the compatibility of an aluminum-plastic film with an electrolyte according to claim 3, characterized in that: The first test sample is a square aluminum-plastic film, and the predetermined size is 100 mm long*15 mm wide.

8. A method for rapidly evaluating the compatibility of an aluminum-plastic film with an electrolyte according to claim 7, characterized in that: The aluminum-plastic film bag filled with electrolyte is immersed in a predetermined ambient temperature for a predetermined period of time, specifically: the aluminum-plastic film bag filled with electrolyte is immersed in an ambient temperature of 30 to 85° C. for 24 to 72 hours; The step of cutting the aluminum-plastic film bag soaked in the electrolyte into a plurality of second test samples of the predetermined size specifically comprises: After the aluminum-plastic film bag filled with electrolyte is immersed in a predetermined ambient temperature for a predetermined time, the electrolyte is poured out; The portion of the aluminum-plastic film bag soaked in the electrolyte was cut into a number of second test samples in a square shape with a size of 100 mm long and 15 mm wide.

9. The method for rapidly evaluating the compatibility of an aluminum-plastic film with an electrolyte according to claim 1, characterized in that: If the melting point, infrared spectrum and secondary sealing sol effect of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted do not change, before judging whether F3 / F1 is greater than a preset first threshold value and F4 / F2 is greater than a preset second threshold value, the method further includes: Compare the melting point, infrared spectrum and secondary sealing sol effect of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted to determine whether there is no change; If so, determine whether F3 / F1 is greater than a preset first threshold, and F4 / F2 is greater than a preset second threshold; If not, it is determined that the electrolyte to be adapted is an electrolyte that is not compatible with the aluminum-plastic film to be adapted.

10. A device for quickly evaluating the compatibility of aluminum-plastic film and electrolyte, characterized in that: include: DSC differential scanning calorimeter, used to measure the melting point of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted; Infrared chromatograph, used to test the melting point and infrared spectrum of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted; A tensile testing machine is used to test the peeling force between the PP layer and the aluminum layer of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted, and to test the tensile force of the second sealing sol of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted; A battery secondary sealing machine is used to perform secondary sealing on the aluminum-plastic film to be adapted before and after being soaked in the electrolyte to be adapted; A camera assembly, used to photograph the secondary sol effect of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted; A data processing terminal equipped with a display module is used to compare the melting point, infrared spectrum and secondary sol effect of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted, and determine whether there is no change; and for determining whether F3 / F1 is greater than a preset first threshold, and F4 / F2 is greater than a preset second threshold; The data processing terminal is used to display a first prompt message on its display module when the melting point, infrared spectrum and second sealing sol effect of the aluminum-plastic film to be adapted before and after being immersed in the electrolyte to be adapted change, and / or F3 / F1 is less than or equal to a preset first threshold, and / or F4 / F2 is less than or equal to a preset second threshold; Otherwise, display a second prompt message on its display module; The first prompt information is used to prompt that the electrolyte to be adapted is an electrolyte that is not compatible with the aluminum-plastic film to be adapted, and the second prompt information is used to prompt that the electrolyte to be adapted is an electrolyte that is compatible with the aluminum-plastic film to be adapted; Wherein, the second threshold is greater than the first threshold; F1 is the peeling force between the PP layer and the aluminum layer of the aluminum-plastic film before being immersed in the electrolyte to be adapted, and F3 is the peeling force between the PP layer and the aluminum layer of the aluminum-plastic film after being immersed in the electrolyte to be adapted; F2 is the secondary sol tensile force between the PP layer and the aluminum layer of the aluminum-plastic film before it is immersed in the electrolyte to be adapted, and F4 is the secondary sol tensile force between the PP layer and the aluminum layer of the aluminum-plastic film after it is immersed in the electrolyte to be adapted.